Toward an outward-oriented development strategy for small states : issues, opportunities, and resilience building : a review of the small states agenda proposed in the Commonwealth/World Bank Joint Task Force report of April 2000 : final report - Briguglio, Lino ([s.n.] [S.l.], 2006)
Summarizes briefly, the overall economic and social performance of small states since 2000. Assesses the response of the states and the international community to the agenda identified in the April 2000 Joint Task Force report and attempts to determine whether its analysis and agenda remain relevant. Highlights some important issues and opportunities that have emerged since 2000 and recommends a revised agenda with priority action items for small states and their development partners.